2015
DOI: 10.1007/s10533-015-0071-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial controls on dissolved organic carbon in upland waters inferred from a simple statistical model

Abstract: Because of the implications for drinking water treatment and supply there is increasing interest in the potential for mitigation through local land management, and for forecasting the likely impact of environmental change.However, the dominant controls on DOC production remain unresolved, hindering the establishment of appropriate reference levels for specific locations. Here we demonstrate that spatial variation in long-term average DOC levels draining upland UK catchments is highly predictable using a simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…Most of the Adirondack lakes including Arbutus Lake have shown significant decreases in sulfate concentration (Park et al, 2003; 0.87 * * * Driscoll et al, 2007). The effects of changes of acidic deposition on surface water, including trends in DOC concentrations, have been documented in North America and Europe (Erlandsson et al, 2011;Evans et al, 2007;Kalbitz et al, 2000;Monteith et al, 2007Monteith et al, , 2015Mulder et al, 2001). However, for Arbutus Lake the effects of changes in acidic deposition may be less evident due to its relatively high pH (∼ 6.7) and ANC (∼ 77 µeq L −1 ) values and base status (Foster et al, 1992;Johnson and Lindberg, 1992;Mitchell et al, 2001;Chen et al, 2004;NYSERDA, 2011).…”
Section: Long-term Change Of Doc Export From the Lakementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the Adirondack lakes including Arbutus Lake have shown significant decreases in sulfate concentration (Park et al, 2003; 0.87 * * * Driscoll et al, 2007). The effects of changes of acidic deposition on surface water, including trends in DOC concentrations, have been documented in North America and Europe (Erlandsson et al, 2011;Evans et al, 2007;Kalbitz et al, 2000;Monteith et al, 2007Monteith et al, , 2015Mulder et al, 2001). However, for Arbutus Lake the effects of changes in acidic deposition may be less evident due to its relatively high pH (∼ 6.7) and ANC (∼ 77 µeq L −1 ) values and base status (Foster et al, 1992;Johnson and Lindberg, 1992;Mitchell et al, 2001;Chen et al, 2004;NYSERDA, 2011).…”
Section: Long-term Change Of Doc Export From the Lakementioning
confidence: 99%
“…There has been considerable discussion on the mechanisms driving recent increases of DOC in acid-sensitive surface waters in North America and Europe Erlandsson et al, 2011;Evans et al, 2007;Monteith et al, 2007Monteith et al, , 2015. For example, Monteith et al (2007) suggested that the recovery of the previous acidification of surface water in response to decreased acidic deposition might result from an increase in the solubility of soil organic matter due to the change of pH, aluminum and ionic strength (Kalbitz et al, 2000;Mulder et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In these high rainfall environments, peat soils dominate many reservoir catchments. This soil type is almost entirely organic and leaches high concentrations of DOC to freshwaters; DOC export has been shown to be linearly related to the percentage cover of peatlands within the catchment (Urban et al, 1989; Dillon and Molot, 1997; Monteith et al, 2015). Because long‐term increases in DOC have been greatest in regions where many organic soils such as peats dominate, there are concerns within the UK water industry that the treatment of water will become progressively more costly (Ritson et al, 2014).…”
mentioning
confidence: 99%
“…Similarly, TOC concentration is primarily an intrinsic feature of the site that is controlled by catchment characteristics (see, for example Monteith et al, 2015). TOC concentrations have approximately doubled at most UWMN sites over the first 2 decades of monitoring, a feature that is thought to be directly linked to reductions in acid deposition .…”
Section: Calculation Of Eqrs and Class Boundariesmentioning
confidence: 99%